rapidSTRIPE H1N1 Test for Detection of the Pandemic Swine Origin Influenza A (H1N1) Virus - Patel, Pranav (American Society for Microbiology, 2011)
The rapidSTRIPE H1N1 test, based on a nucleic acid lateral-flow assay, has been developed for diagnosis of a swine-origin influenza A (H1N1) virus. This test is simple and cost-effective and allows specific detection of the S-OIV A (H1N1) virus from swab sampling to final detection on a lateral-flow stripe within 2 to 3 h.